Hemoperfusion during veno-venous ECMO in severe COVID-19 with IL-6 elevation. (April 2022) - Giordano, Giovanni; Alessandri, Francesco; Pugliese, Francesco
Highlights: IL-6 might be a target of specific intervention in severe COVID-19. Hemoperfusion and anti IL-6 drugs use have been reported in COVID-19 patients. vv-ECMO support might worsen COVID-19-related cytokine release syndrome. HA-380 hemoperfusion filter reduces IL-6 concentration. Hemodynamic, renal and chest X ray improvement might be related to cytokines removal.